Myrrh a traditional medicine or a multipurpose pharmaceutical excipient - Fatemeh Erfanfar; Hashem Montaseri; Abdolali Mohagheghzadeh; Ayda Hosseinkhani (Shiraz University of Medical Sciences, 2015)
Introduction: A drug dosage form contains excipients as well as active pharmaceutical ingredients. Formerly excipients were considered as inert components which were used by a formulator to provide suitable volume, weight and consistency of a dosage form. Today however, excipients are expected to perform multifunctional roles such as enhancing physical, chemical and microbial stability of the dosage form, improving the color or odor of the formulation and influencing the release and bioavailability of the active ingredient. Among various excipients, natural ones seem to be more beneficial to use, since they are economical, safe, biodegradable and biocompatible. In this article, Myrrh oleo- gum- rein is introduced as a potential natural multipurpose excipient that can perform many useful roles in pharmaceutical dosage forms.Materials and methods: Scopus and Google scholar electronic databases were searched to find different properties of myrrh as an excipient. Also ten famous traditional Iranian medicine books were studied to find semisolid formulations named Sabgh which contained myrrh. One of these formulations was prepared and its physical and microbiological stability was assessed. The role of myrrh as an excipient in this formulation was discussed. Results and discussion: Antibacterial and preservative effects shown in the formulation were related to the essential oils of myrrh. The gum portion was found to be a potential surfactant. In addition, myrrh is a natural muco-adhesive and film forming material. These properties were observed for myrrh in the Sabgh formulated in this study as well. So we can conclude that myrrh can be a potential multipurpose excipient in pharmaceutical industries which needs further research.